Handbook of research on trends and future directions in big data and web intelligence - Zaman, N. (IGI Global, 2015)
Big data is a well-trafficked subject in recent IT discourse and does not lack for current research. In fact, there is such a surfeit of material related to big data-and so much of it of questionably reliability, thanks to the high-gloss efforts of savvy tech-marketing gurus-that it can, at times, be difficult for a serious academician to navigate. The Handbook of Research on Trends and Future Directions in Big Data and Web Intelligence cuts through the haze of glitz and pomp surrounding big data and offers a simple, straightforward reference-source of practical academic utility. Covering such topics as cloud computing, parallel computing, natural language processing, and personalized medicine, this volume presents an overview of current research, insight into recent advances, and gaps in the literature indicative of opportunities for future inquiry and is targeted toward a broad, interdisciplinary audience of students, academics, researchers, and professionals in fields of IT, networking, and data-analytics. Â© 2015, IGI Global. All rights reserved.